Multiplex-PCR technique to predict polymorphic antigens – M, N, S and s – and associations between their alleles and Mia-associated hybrid glycophorins - Thanaporn Kerdthip; Oytip Nathalang; Sarisa Chidtrakoon; Tanaporn Choychimplee; Dollapak Apipongrat; Kamphon Intharanut (Scientific Reports)
Abstract Serological typing of MNS polymorphic antigens – M, N, S and s – remains a fundamental technique in transfusion medicine and prenatal care, providing essential information for matching blood donors and recipients and managing haemolytic disease. Although this method is well proven and routinely used, it is not a comprehensive solution, as it has several weaknesses. Alternatively, multiplex polymerase chain reaction (PCR) is a commonly used genotyping tool due to its potency and ability to amplify several DNA targets simultaneously in a single reaction. In this work, we aimed to develop multiplex PCR and evaluate its performance for GYPA*M, GYPA*N, GYPB*S, and GYPB*s allele identification using serological and DNA sequencing methods. We also aimed to investigate the correlation between these alleles and Mia-associated hybrid glycophorins (GPs). Remarkably, multiplex PCR was well optimised, and the results aligned with serological phenotyping and DNA sequencing data with maximum accuracy and reliability; this confirmed our findings on its validity in predicting MNSs phenotypes. In addition, this work strongly demonstrates, for the first time, a moderate correlation between the GYPA*M/M and GYPB*s/s genotypes and Mia-associated hybrid GPs among Thai donors. Individuals with the GYPA*M/M and GYPB*s/s genotypes, predicted M + N − S− s + phenotypes, will thus most likely to express the Mi(a+) antigen. Nevertheless, further studies are required to validate these results and elucidate the underlying correlations.